Establishing a quality management system in a fertility center: experience with ISO 9001 - Bento,Fabiola C. (2016)
In Fertility Centers, quality should be measured by how well the organization complies with pre-defined requirements, and by how quality policies are implemented and quality objectives achieved. Having a quality management system (QMS) is a mandatory requirement for IVF centers established in most countries with regulatory guidelines, including Brazil. Nevertheless, none of the regulatory directives specify what a QMS must have in detail or how it should be implemented and/or maintained. ISO 9001 is the most important and widespread international requirement for quality management. ISO 9001 standards are generic and applicable to all organizations in any economic sector, including IVF centers. In this review, we discuss how we implemented QMS according to ISO 9001 and what we achieved 5 years later. In brief, with ISO we defined our structure, policies, procedures, processes and resources needed to implement quality management. In addition, we determined the quality orientation of our center and the quality objectives and indicators used to guarantee that a high-quality service is provided. Once measuring progress became part of our daily routine, quantifying and evaluating the organization's success and how much improvement has been achieved was an inevitable result of our well-established QMS. Several lessons were learned throughout our quality journey, but foremost among them was the creation of an internal environment with unity of purpose and direction; this has in fact been the key to achieving the organization's goals.